Communication as a prerequisite for forming online learning communities: a case study - Giannakopoulou, Eleni (Adult Education Critical Issues, 2024)
Many researchers and educators have emphasized the importance of forming and developing online learning communities. Moreover, the leading role that the forms and the contents of communication between learners have in the creation and functioning of these communities is stressed. In this paper we present and comment on s, the findings of a research project that studied the aforementioned communication issues between students of undergraduate and postgraduate courses, at the Hellenic Open University. The analysis of the empirical data of this research, shows that the role of communication in the educational activities in which the subjects of our research were involved is extremely weak and consequently the formation of online learning communities is rudimentary.